Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1177/03635465010290021701
|View full text |Cite
|
Sign up to set email alerts
|

Inversion and Eversion Strengths in the Weightbearing Ankle of Young Women

Abstract: Maximum isometric ankle inversion and eversion muscle strengths were measured under full unipedal weightbearing in 20 healthy young adult women. When the women wore a low-top shoe, the mean (standard deviation) maximum external eversion moments resisted with the foot in 0 degrees and 32 degrees of ankle plantar flexion were 24.1 (7.6) and 24.1 (8.1) N x m, respectively, while the corresponding values for maximum inversion moments resisted were 14.7 (6.8) and 17.4 (6.4) N x m, respectively. Both shoe height and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…However, estimating the values experimentally has limitations as well, with an extremely large amount of variability due to the different muscle strength and mental concentration of subjects. In past studies on hip and ankle strength, researchers have only examined strength under isometric or isokinetic loading, not stiffness (Brand et al, 1986;Fredericson et al, 2000;Jaramillo et al, 1994;Munn et al, 2003;Neumann et al, 1988;Ottaviani et al, 2001). To assure that the loading conditions at the hip and ankle used in this study were reasonable and realistic, the maximum torques generated at the hip and ankle were compared to reported values of maximum isometric frontal-plane strength (Markhede and Grimby, 1980;Ottaviani et al, 2001) and shown to be far below these reported values (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…However, estimating the values experimentally has limitations as well, with an extremely large amount of variability due to the different muscle strength and mental concentration of subjects. In past studies on hip and ankle strength, researchers have only examined strength under isometric or isokinetic loading, not stiffness (Brand et al, 1986;Fredericson et al, 2000;Jaramillo et al, 1994;Munn et al, 2003;Neumann et al, 1988;Ottaviani et al, 2001). To assure that the loading conditions at the hip and ankle used in this study were reasonable and realistic, the maximum torques generated at the hip and ankle were compared to reported values of maximum isometric frontal-plane strength (Markhede and Grimby, 1980;Ottaviani et al, 2001) and shown to be far below these reported values (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…The air stirrup brace was set so the heel was approximately 10 cm above the resistance plate, resulting in varying degrees of plantar flexion from 30 to 45 degrees depending on foot size. Because the ankle plantarflexion angle has little influence on PT muscle length, the influence of ankle plantarflexion on isometric strength was assumed to be negligible 6,14,20…”
Section: Methodsmentioning
confidence: 99%
“…In addition, no subjects reported discomfort due to forced foot inversion or eversion on the irregular surface. Hence, the risk for ankle sprain was reduced to acceptable levels by restricting the irregular surface prism heights to 1.5 cm [37].…”
Section: Limitationsmentioning
confidence: 99%